Gender Gap in Access to Education in Kazakhstan - Z. T. Satpayeva; G. S. Nygymetov (Экономика: стратегия и практика)
Gender inequality in education is a problem in both developed and developing countries. This social phenomenon has many negative consequences (income inequality, decline in human capital, reduction in economic growth, etc.). The purpose of this study is to identify the gender inequality in education through the analysis of gender gaps in access to education in Kazakhstan. The study was conducted within the concept of liberal feminism to assess the participation of women in education. Issues of gender inequality in education were studied through the gender parity index, with a focus on the analysis of the enrollment of women and men in education and their satisfaction with the availability of educational services. The main research methods were economic and statistical analysis and comparison. The source base for the study was statistical data from the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan for the period from 2000 to 2022. The limitation of the study was the lack of data for a certain period or by level of education. The study revealed that in Kazakhstan there is a gender inequality in the field of postgraduate education, where the number of students is dominated by women. During the period under review, gender inequality decreased at the master’s level and increased at the doctoral level. At the same time, during the pandemic, gender inequality in education at the master’s level increased, while at the doctoral level it decreased. The main reason for the emergence of gender inequality in the field of postgraduate education is the low attractiveness of employment in the field of education and science on the part of men due to the low level of income in this area. The results obtained indicate the need to increase the prestige of teaching and research activities among the population, including by raising wages and providing decent social security for specialists in this field.